2020
DOI: 10.2495/epm200111
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Approach to Efficiency Assessment of Investment Projects in the Energy Sector

Abstract: According to the annual world statistics, primary energy consumption demonstrated a steady growth over the past decade but in 2018, its average value was doubled. A rapid development of energy sector will not only lead to the growth of CO2 emissions and other negative consequences, but also to more intensive use of natural resources in the immediate future. Growing pressure on resources might give rise to a number of challenges in virtually all branches of human activity. The energy sector's impact on the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The proposed system of ecological indicators can be also adapted to the type of investment project and the branch of the economy to which this investment project belongs. An example of adaptation is given in the paper "Improving the approach to efficiency assessment of investment projects in the energy sector" [40], where indicators of the natural capital use were adapted to the energy facility.…”
Section: Indicators Of Energy Efficiencymentioning
confidence: 99%
“…The proposed system of ecological indicators can be also adapted to the type of investment project and the branch of the economy to which this investment project belongs. An example of adaptation is given in the paper "Improving the approach to efficiency assessment of investment projects in the energy sector" [40], where indicators of the natural capital use were adapted to the energy facility.…”
Section: Indicators Of Energy Efficiencymentioning
confidence: 99%
“…Finally, improving renewables development across US, Indian, and Chinese domains is impossible without tackling a significant impediment. Globally, the absence of economic incentives, the significant startup costs, and inadequate return on medium-term renewable energy expenditures (particularly solar) (Karaeva et al, 2020;Shahzad et al, 2021). However, Elavarasan et al (2020) found that problem of inadequate usage are two main impediments to renewable power in China, whereas the underexploited generating potential is expected to undermine hydropower and solar power implementation in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, current approaches to the appraisal of environmental and economic efficiency do not consider the specifics of various sectors of the economy, which complicates the comparison between alternative investment projects and negatively affects the effectiveness of decisions taken at the stage of their selection [ 8 , 9 , 10 ]. It is therefore necessary to develop simplified approaches to consider the specifics of economic sectors in order to improve the effectiveness of environmental performance assessment and the possibility of visual comparison of projects by their environmental component [ 11 ].…”
Section: Introductionmentioning
confidence: 99%